Landslides on Ceres: Inferences Into Ice Content and Layering in the Upper Crust. Issue 6 (11th June 2019) - Chilton, H. T.; Schmidt, B. E.; Duarte, K.; Ferrier, K. L.; Hughson, K. H. G.; Scully, J. E. C.; Wray, J. J.; Sizemore, H. G.; Nathues, A.; Platz, T.; Schorghofer, N.; Schenk, P. M.; et al.
Abstract: We analyze landslides on Ceres using several quantitative approaches to constrain the composition and structure of the top few kilometers of Ceres' crust. We focus on a subset of archetypal landslides classified morphologically as thick, steep‐snouted "type 1" (T1) flows and thin spatulate "type 2" (T2) flows (Schmidt et al., 2017, https://doi.org/10.1038/ngeo2936 ) to explore the landslides' mechanical properties. Our results confirm earlier observations showing that T1 landslides are typically found poleward of 70° latitude and T2 mostly equatorward of 70° latitude. Measurements of landslide drop height and runout length imply effective friction coefficients lower than common friction coefficients in any of Ceres' identified or suggested non‐ice surface materials, including saturated clays. Our measurements of the volume and area of landslide scars suggest that T1 landslides can fail to greater depths than T2 for a given scar area, consistent with depth‐limited failure in T2 landslides. These results are consistent with a layer of lower shear strength material overlying a stronger layer in Ceres' outer shell at low to middle latitudes and a single layer without an overlying weak layer at polar latitudes. Combining these observations with known constraints on Ceres' near‐surface composition, we propose that Ceres' crust at low to middle latitudes consists of a topmost layer with an ice content in excess of the spectral and elemental detection depths, thins out at high latitudes, and overlies a stronger and more ice‐rich layer. Plan Language Summary: We use landslides on Ceres to explore the possible ice content and distribution in the upper few kilometers of Ceres. The landslides used here are a subset of the best examples of the main types of landslides identified in earlier work. We confirm that type 1 landslides are only common poleward of 70° latitude and type 2 landslides are commonly equatorward of 70° latitude. Friction coefficients estimated from the landslide drop height and runout length span a range suggestive of ice. Volume and area measurements of the landslide failure scar are consistent with a weak layer overlying a stronger layer at latitudes where type 2 landslides are common and a single layer in the case of type 1 landslides, located primarily in polar latitudes. We propose that the weak layer suggested at middle and low latitudes thins out at the poles and that the stronger layer has higher ice content. Key Points: Landslide types 1 and 2 mobilities are consistent with cold ice and warm ice respectively, with significant overlap Type 2 landslides are consistent with a layer of weaker shear strength overlying a stronger one, which we suggest thins out by 70° latitude We propose the low shear strength layer contains 3–19 vol% ice with the underlying layer composed of 24–40 vol% ice